MOTIVASI PERNIKAHAN DI KALANGAN MAHASISWA FKIP UNIVERSITAS RIAU - Yenni Wahyuni; Rosmawati Rosmawati; Tri Umari (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2018)
Abstract: Marriage was a legally bond which gives birth to the family as the foundation of the life of society and state. The existence of a family marked or detected by a marriage contract, which is a requirement for forming a family. Person will have a new status as husband for man and wife for woman after getting marriage. In term of marriage, there may have strong motivation while making decision to get married especially for the student, because finishing the study is the main assignment for them. Hence, they looking for a job, work on their field to apply their knowledge then able to fill their needs. There were married students in FKIP S1 at University of Riau. This study aims to determine the motivation of married students during the study period, to determine the benefits and barriers to marriage during the study period. Research subjects were female students who had married during the study at the University of Riau as many as 8 people with age criteria ≤ 22 years. The method used is descriptive qualitative. Sampling in this research is done by Snowball Sampling. Research data obtained through interviews and documentation. The results indicate that the motivation of married students during the majority of study because of the avoidance of adultery, feel fit and need a partner, get offspring, and get support from the family. The benefits of marriage in the study period is more motivated to finish college, life becomes more peaceful and calm. In this study the majority of students declare no obstacles in their studies, marriage is not an obstacle in completing the lecture even they are motivated to complete college.Key Words: Motivation, Marriage